2012
DOI: 10.1016/j.thromres.2011.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell tissue factor does not contribute to venous thrombogenesis in an electrolytic injury model

Abstract: Introduction Tissue factor (TF) is a potent initiator of the extrinsic coagulation cascade. The role and source of TF in venous thrombotic disease is not clearly defined. Our study objective was to identify the contribution of myeloid cell TF to venous thrombogenesis in mice. Materials and Methods The mouse electrolytic inferior vena cava model was used to induce thrombosis. The following groups of mice were used (1) TFflox/floxLysMCre+ mice that have reduced TF expression in myeloid cells, (2) TFflox/floxLy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies with healthy mice have shown that leukocyte TF contributes to thrombosis in the inferior vena cava (IVC) stenosis model, whereas vessel wall TF drives thrombosis in the IVC ligation and electrolytic injury models. [34][35][36][37][38] In small vessels, thrombosis has been shown to be dependent on TF expression by neutrophils, hematopoietic cell-derived TF-positive MPs, and vessel wall TF.…”
Section: Development Of a Venous Thrombusmentioning
confidence: 99%
“…Studies with healthy mice have shown that leukocyte TF contributes to thrombosis in the inferior vena cava (IVC) stenosis model, whereas vessel wall TF drives thrombosis in the IVC ligation and electrolytic injury models. [34][35][36][37][38] In small vessels, thrombosis has been shown to be dependent on TF expression by neutrophils, hematopoietic cell-derived TF-positive MPs, and vessel wall TF.…”
Section: Development Of a Venous Thrombusmentioning
confidence: 99%
“…28 Indeed, vessel wall TF, but not myeloid cell TF, has been shown to drive thrombosis in the IVC stasis model, whereas myeloid cell TF contributes to thrombosis in the IVC stenosis model. 17,28,29 It is, therefore, not surprising that a role for FXII and FXI cannot be detected in this model. Moreover, it has previously been shown that the IVC stasis model is insensitive to neutrophil depletion, platelet depletion, or inhibition of platelet activation.…”
Section: Discussionmentioning
confidence: 88%
“…The cauterization of back branches and the full ligation of the IVC in this model likely exposes significant amounts of subendothelial TF that may trigger thrombosis 28 . Indeed, vessel wall TF, but not myeloid cell TF, has been shown to drive thrombosis in the IVC stasis model, whereas myeloid cell TF contributes to thrombosis in the IVC stenosis model 17,28,29 . It is, therefore, not surprising that a role for FXII and FXI cannot be detected in this model.…”
Section: Discussionmentioning
confidence: 90%